Rola Boga i palingenezy w kształtowaniu się poglądów filozoficznych Augusta Cieszkowskiego (Przegląd Religioznawczy – The Religious Studies Review, 2019)
The aim of the paper is to reflect on the specificity of the evolution of August Cieszkowski’s philosophical views. In the presented research perspective the very essence of this evolution lays in progressive distancing from the Hegelianism and in unorthodox turn towards religious sphere in a broad sense. This point of view underlines the fundamental meaning of God and Palingenesis, Cieszkowski’s work published in 1842 in which he directly formulates accusation towards Hegelian school for its abstractness and one-sided intellectualism. This work also sketches a postulate of creating new, synthetic form of reflection, that avoids limitations of both religious orthodoxy and philosophical speculation. The effort of creating such form delineates the specificity of Cieszkowski’s further output.